IoT implementation in Malaysian SMEs: A strategic analysis of enablers and challenges - Wong, Yan Chiew; Md Saad, Mohd Shamsuri; Othman, Mohd Azlishah; Awang Md Isa, Azmi; Md Saat, Mohd Shakir; Othman, Ahmad Fauzan; Othman, Mazlin; Zaini, Zati Hanani; Salakin, Zurina; Mahalingam, Tamilselvan (Penerbit Universiti Teknikal Malaysia Melaka, 2025)
This study investigates the patterns and determinants of Internet of Things (IoT) adoption among Malaysian small-to-medium enterprises (SMEs), examining organizational characteristics and implementation dynamics. Through comprehensive analysis, the research evaluates critical factors influencing IoT integration, encompassing external pressures, regulatory support mechanisms, technical capabilities, and organizational preparedness. The findings demonstrate that organizational age and size significantly influence IoT adoption propensity, with younger and smaller SMEs exhibiting greater inclination toward Industrial and Retail IoT implementations, primarily motivated by operational efficiency imperatives. While middle management emerges as crucial facilitators of IoT deployment, the study reveals significant disparities in workforce engagement and competency development. Implementation challenges persist across multiple dimensions, including financial constraints, technical complexity, and system compatibility issues. These findings underscore the necessity for targeted policy interventions, industry-specific capability development programs, and adaptable IoT solutions. The research highlights the strategic importance of leadership commitment, resource optimization, and ecosystem support in accelerating IoT adoption among Malaysian SMEs.